Comparative proteomic analysis of two distinct stem-cell populations from human amniotic fluid1. Issue 6 (19th June 2015) - Romani, Rita; Fallarino, Francesca; Pirisinu, Irene; Calvitti, Mario; Caselli, Anna; Fiaschi, Tania; Gamberi, Tania; Matino, Davide; Talesa, Vincenzo N.; Donti, Emilio; Puccetti, Paolo; Modesti, Alessandra; et al.
<x xml:space="preserve">Abstract</x> Characterization of two types of stem cells isolated from human amniotic fluid.